Review cyclic peptides on a merry‐go‐round; towards drug design. Issue 5 (September 2015) - Tapeinou, Anthi; Matsoukas, Minos‐Timotheos; Simal, Carmen; Tselios, Theodore
ABSTRACT: Peptides and proteins are attractive initial leads for the rational design of bioactive molecules. Several natural cyclic peptides have recently emerged as templates for drug design due to their resistance to chemical or enzymatic hydrolysis and high selectivity to receptors. The development of practical protocols that mimic the power of nature's strategies remains paramount for the advancement of novel peptide‐based drugs. The de novo design of peptide mimetics (nonpeptide molecules or cyclic peptides) for the synthesis of linear or cyclic peptides has enhanced the progress of therapeutics and diverse areas of science and technology. In the case of metabolically unstable peptide ligands, the rational design and synthesis of cyclic peptide analogues has turned into an alternative approach for improved biological activity. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 104: 453–461, 2015.